2001
DOI: 10.1002/jctb.501
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic remediation of lead‐, zinc‐ and cadmium‐contaminated soil

Abstract: Electrokinetic remediation of lead-, zinc-and cadmium-contaminated sand and clayey soils has been investigated under laboratory-scale conditions. Soil extracts of heavy metals (by 1 M HCl solution) were analysed by optical emission spectrometry. The ef®ciency of electrochemical remediation was partially dependent on the pH of the soil media. With pH increase, the migration of heavy metal ions toward the cathode was limited. When acetic acid was added to the sandy soil, almost complete remediation was achieved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…In addition, slight differences can be observed between the distribution of Cd and Zn for all three experiments. The mobility of Cd and Zn through the soil followed the same pattern [29]. These findings are consistent with previous studies conducted in lab-scale electrokinetic experiments with chelate agents conditioning the cathode compartment.…”
Section: Distribution Of Cadmium Nickel and Zinc In The Soil Cellsupporting
confidence: 91%
“…In addition, slight differences can be observed between the distribution of Cd and Zn for all three experiments. The mobility of Cd and Zn through the soil followed the same pattern [29]. These findings are consistent with previous studies conducted in lab-scale electrokinetic experiments with chelate agents conditioning the cathode compartment.…”
Section: Distribution Of Cadmium Nickel and Zinc In The Soil Cellsupporting
confidence: 91%
“…Although, most of the investigations were done on soils contaminated with single metallic species [4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21]26,38], limited tests have been done on soils contaminated with multiple metallic species [10,[22][23][24][25][27][28][29][30][31][32][33][34][35][36][37]. Previous tests conducted on soils contaminated with multiple species have shown that, the presence of multiple metals had an impact on the removal efficiencies [34].…”
Section: Previous Researchmentioning
confidence: 99%
“…The electrokinetic process is a great promise for remediation of polluted soils, as it has high removal efficiency and time effectiveness in low permeability soils [6]. Electrokinetic remediation can be used to treat soils contaminated with inorganic species [7][8][9][10][11][12][13], organic compounds [14][15][16] and radionuclides [17,18].…”
Section: Introductionmentioning
confidence: 99%